m-DAL v2: modular multi channel data logger with smart monitoring system / Azran Mansor ... [et al.] - Mansor, Azran; Ilias, Nur Hanim; Shahidan, Mohd Fairuz; Amir, Atikah Fukaihah; Mat Nayan, Nadiyanti (2024)
This project introduces the Modular Multichannel Data Logger (m-DAL), a versatile system tailored to assess herbaceous roof ecosystems' services. Unlike conventional and expensive data loggers, m-DAL allows for concurrent measurements across multiple channels at a fraction of the cost, while enhancing adaptability and modularity. It is capable of gathering real-time ambient plant temperature and relative humidity data, enabling the investigation of leaf transpiration cooling through water supply manipulation in tropical climates. Utilizing open-source technology, it incorporates an Arduino Giga R1 Wi-Fi microcontroller board interfaced with twelve channels, including type-K thermocouples with MAX6675 amplifiers and DHT22 sensors, with real-time monitoring via the Arduino IoT Cloud. Calibration is conducted using a two-point cross-calibration method with the Ambient Weather WH32B Thermometer-Barometer-Hygrometer for accuracy ranging from 96.15% to 99.72% for temperature sensors and 97.46% to 97.55% for humidity sensors. In field testing, it effectively demonstrates its capabilities in data collection, logging, real-time monitoring, environmental tracking, data storage, retrieval, validation, and cost-effectiveness. Finally, the recorded data offers opportunities for further analysis and modeling of herbaceous transpiration cooling as an ecosystem service. Embrace the versatility of the m-DAL for ecological research and beyond.